Análise das viabilidades de implantação e operação de rede semipública de transprte coletivo em Uberlândia, MG - Nogueira, Luciano (2015)
The aim of this work is to study the economic-financialviability to deploy and operate a paratransit network to meet demands of commuting trips for employees of a private company in Uberlândia, MG. The study was developed based on employees who leave in the Santa Mônica neighborhood, whose addresses were geocoded and inputted on a digital map. The information was inputted in the TransCAD software in order to determine clusters corresponding to bus stops considering the maximum walking distance for passengers to have access to the service. Optimization studies of routing and trip times were done, taking into account the vehicle capacity as a parameter, which allowed for the scheduling of the transportation service. Once calculated the operational parameters, the fares were calculated by using the methodology adopted by GEIPOT. In the end, it was performed an economic and financial viability of implementing and operating the paratransit service. It was compared the amounts incurred by the company in funding the Vale-Transporte Program with those indicated in the farestudies. The work concluded that the company could deploy and maintain their own network to transport its employees, with equivalent costs, if compared to Vale-Transporte Program, and higher service level, if compared to regular bus service.